2021
DOI: 10.21608/jmals.2021.200216
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer levels in COVID-19 out-hospitalized patients in Egypt

Abstract: Background:The D-dimer is formed by the activation of the plasmin enzyme, and elevated levels indicate that there is a hypercoagulable state and secondary fibrinolysis in the body, which is extremely useful for the diagnosis of thrombotic diseases. Patients with COVID-19 were reported to have a hypercoagulable state. Patients and methods: This study included 231 out hospitalized patients with confirmed COVID-19 infection in Alexandria, Egypt, these study subjects were randomly selected irrespective of the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This (14) , LDH has a high level in 67.7% (P-value 0.024) (15) , and D-dimer has positive results in 36.4% (P-value 0.00001) (16) , Similar to our study Mo et al, reported normal thrombocyte count in 70 cases mild infection and slightly lower in 85 severe cases (17) .…”
Section: Discussionsupporting
confidence: 85%
“…This (14) , LDH has a high level in 67.7% (P-value 0.024) (15) , and D-dimer has positive results in 36.4% (P-value 0.00001) (16) , Similar to our study Mo et al, reported normal thrombocyte count in 70 cases mild infection and slightly lower in 85 severe cases (17) .…”
Section: Discussionsupporting
confidence: 85%
“…The expression of TNF-𝛼 is increased during lung injury, where it provokes a variety of biological responses to modulate the anomaly by inducing the expression of numerous other inflammatory mediators, which is a key step consisting of stimulating multiple genes involved in protective processes (19) . It was noticed that patients with COVID-19 demonstrated significantly elevated levels of TNF-𝛼 upon admission to hospitals (20) , this study was conducted on thrombocytopenia was not significant also with mild COVID-19 infection (21) , but CRP has a sensitivity 90.2% (22) , while other biomarkers have different sensitivity in mild COVID-19 infection as ferritin which has a sensitivity of 71.4% (23) , LDH has a sensitivity 67.7% (24) , and D-dimer has a sensitivity 36.4% (25) .…”
Section: Discussionmentioning
confidence: 89%
“…This study reveals a high level of CRP in 296 patients (90.2%) with a sensitivity of 90.2%, which is divided into two groups the first have CRP levels 5-100 (56.1%) and the second group has CRP levels more than 100 (34.1%), the high-level CRP was a significant biomarker for COVID-19 diagnosis or prognosis in out-hospitalized patients (Outpatients and patients under home observation), with a p-value is p is < .00001which less than 0.05. CRP showed a sensitivity of 90.2% in COVID-19 mild infection patients which was more than other biomarkers such as ferritin which has a sensitivity of 71.4% (13) , LDH has a sensitivity of 67.7% (14) , and D.dimer has a sensitivity 36.4% (15) with mild COVID-19 infection patients. Furthermore, a study of 27 COVID-19 patients from China found that CRP levels >20.4 mg/L were 83.0% sensitive and 91.0% specific when predicting severe COVID-19 infection (16) .…”
Section: Discussionmentioning
confidence: 95%